ON BECOMING CULTURAL TRANSLATION - Aranda, Lucía (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Translation is much more than the linguistic transference between two languages: it is a cultural activity, rich in choices and consequences. Literature reflects the art and culture of a time and is fueled by translation. By examining which works are translated and the manner of their translation, postcolonial translation offers a framework through which to study their influence on national and world literatures, identities and ideologies. This paper examines the concept of nontranslatability, the original, and the relevance of translation as both an artistic and a political act. Translation is a metaphor for power relations in which culture, not the word, sentence or text is the unit of translation. Resumen La traducción es mucho más que la transferencia lingüística entre dos idiomas: es una actividad cultural, rica en toma de decisiones y consecuencias. La literatura refleja el arte y la cultura de una época dada y se alimenta de la traducción. Al examinar qué obras se traducen y la manera de traducirlas, la traducción postcolonial ofrece un marco a través del cual se puede estudiar cómo han influido dichas traducciones sobre las literaturas nacionales y mundiales, las identidades y las ideologías. Este trabajo examina el concepto de la no-traducción, el original y la relevancia de la traducción como un acto artístico y político. La traducción es una metáfora de las relaciones de poder en la que la cultura es la unidad de traducción, y no la palabra, la frase o el texto.